Counseling to Improve Children's Self-Motivation in Manado During the Pandemic: Penyuluhan Untuk Meningkatkan Motivasi Diri Anak Di Manado Di Masa Pandemi - Kirana, Clarissa Chandra; Salomozs, Gracella; Kurniawan, Ramanda Cahya Perdana; Ramadhani, Talitha Rizky; Faloy, Bledy; Elisya, Chresanty Vidka; Gunadirin, Elly Yuliandari (Universitas Muhammadiyah Sidoarjo, 2025)
Effective education is needed and is also a very important factor for development of a child. It is not uncommon for the educational process that benefits students in school to cause a decrease in motivation because these students do not understand the forms of motivation and ways to increase motivation. Extension is one of the effective intervention methods to increase these variables, through cognitive readiness by providing new insights and information. The subjects of this study were 30 students of SDN 12 Manado. This research is using a pre-experimental study with a pretest posttest group design. Highlights: Motivation Matters – Students often struggle due to a lack of understanding of motivation and how to enhance it. Extension as a Solution – Providing new insights through cognitive readiness can effectively boost motivation. Research-Based Approach – A pre-experimental study on 30 students evaluates the impact of intervention on motivation. Keywords: Increased Self-Motivation, Counseling, Elementary School Students